Earnings management in Libyan commercial banks: perceptions of stakeholders. (2017) - Barghathi, Yasser; Collison, David; Crawford, Louise
The issue of earnings management has continued to be problematic in the financial reporting context. It has proved to be an important topic that concerns a wide range of stakeholders, including regulators, investors and preparers. The objective of this paper is to examine the perceptions of different stakeholders with regard to the financial reporting quality of Libyan commercial banks (LCBs) by addressing the issue of earnings management. The paper adopts a qualitative approach in order to investigate the topic of earnings management. It considers motives for, and techniques of, earnings management as well as the role and potential role for accounting standards and improved corporate governance in addressing the issue. The paper reports on 28 semi-structured interviews with different stakeholders of LCBs. It is found that financial reporting quality is perceived to be impaired as a result of earnings management. It also provides prima facie evidence of some fraudulent activity in the management of earnings. IFRS/IAS as well as a sound corporate governance system is perceived to have an important potential role in improving financial reporting quality. Some confusion and ambiguity in the understanding of the term earnings management was also identified.